1999
DOI: 10.2337/diabetes.48.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Absolute requirement of macrophages for the development and activation of beta-cell cytotoxic CD8+ T-cells in T-cell receptor transgenic NOD mice.

Abstract: The development of autoimmune diabetes in NOD mice results from selective destruction of beta-cells by a T-cell-dependent autoimmune process. However, the mechanisms that control the generation of beta-cell cytotoxic T-cells in vivo are poorly understood. We recently established 8.3-T-cell receptor (TCR)-beta transgenic NOD mice that show a selective acceleration of the recruitment of CD8+ T-cells into the islets of prediabetic animals, resulting in rapid beta-cell destruction and early onset of diabetes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 0 publications
3
66
1
Order By: Relevance
“…Macrophages are the first cells to infiltrate the islets in both NOD mice and BB rats [6,57]. Activated macrophages are toxic to pancreatic islets in vitro [58] and macrophage depletion or inactivation prevent diabetes in BB rats and NOD mice [59,60]. IP-10 was reported to attract monocytes [61], and it is therefore conceivable that the early expression of IP-10 (current data) and MCP-1 [8] by NOD islet cells contributes to the recruitment of macrophages in the early stages of insulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are the first cells to infiltrate the islets in both NOD mice and BB rats [6,57]. Activated macrophages are toxic to pancreatic islets in vitro [58] and macrophage depletion or inactivation prevent diabetes in BB rats and NOD mice [59,60]. IP-10 was reported to attract monocytes [61], and it is therefore conceivable that the early expression of IP-10 (current data) and MCP-1 [8] by NOD islet cells contributes to the recruitment of macrophages in the early stages of insulitis.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, it was recently shown that T cell-derived IFN-␥ is essential for the rejection of tumor allografts, and that this requirement is due to the ability of IFN-␥ to activate cytotoxic macrophages at the graft site (57). Similarly, islet-specific autoimmune pathogenesis by CD8 ϩ T cells in a transgenic model has been shown to be macrophage dependent (58).…”
Section: Discussionmentioning
confidence: 99%
“…29,37 Other groups used clodronate-dependent elimination of macrophages in NOD mice to demonstrate protection from diabetes. 34,39 Here again, young NOD mice that were depleted of macrophages were unable to generate cytotoxic T cells, thereby implicating the macrophage as an essential accessory cell for the differentiation of effector diabetogenic T cells. 34 Moreover, as seen in the previous studies with silica administration, the clodronate-treated NOD mice also exhibited protection from insulitis, 34 which was in agreement with the lack of priming of diabetogenic T cells responsible for recruitment of the inflammatory infiltrate in the pancreas.…”
Section: Macrophages Kill ␤ Cells In T1dm 2143mentioning
confidence: 99%
“…29,34,38,39 Several studies in the past suggested that inhibition of diabetes in macrophagedepleted NOD mice was a likely result of impaired priming and expansion of diabetogenic CD4 ϩ and CD8 ϩ T cells, 34 -36,39 whereas other in vitro assays demonstrated that activated macrophages could lyse pancreatic ␤-tumor cells. 44 -46 For example, the result that depletion of macrophages via silica particles in NOD mice or BB rats resulted in protection from diabetes was interpreted to suggest an important role for macrophages in the priming of diabetogenic T cells.…”
Section: Macrophages Kill ␤ Cells In T1dm 2143mentioning
confidence: 99%
See 1 more Smart Citation